ATTITUDE OF TEACHING FACULTY TOWARDS STATISTICS AT A MEDICAL UNIVERSITY IN KARACHI, PAKISTAN - Khan, Nazeer; Mumtaz, Yasmin (Journal of Ayub Medical College Abbottabad, 2009)
Background: Statistics is mainly used in biological research to verify the clinicians and researchers findings and feelings, and gives scientific validity for their inferences. In Pakistan, the educational curriculum is developed in such a way that the students who are interested in entering in the field of biological sciences do not study mathematics after grade 10. Therefore, due to their fragile background of mathematical skills, the Pakistani medical professionals feel that they do not have adequate base to understand the basic concepts of statistical techniques when they try to use it in their research or read a scientific article. The aim of the study was to assess the attitude of medical faculty towards statistics. Methods: A questionnaire containing 42 close-ended and 4 open-ended questions, related to the attitude and knowledge of statistics, was distributed among the teaching faculty of Dow University of Health Sciences (DUHS). One hundred and sixty-seven filled questionnaires were returned from 374 faculty members (response rate 44.7%). Results: Forty-three percent of the respondents claimed that they had ’˜introductive’ level of statistics courses, 63% of the respondents strongly agreed that a good researcher must have some training in statistics, 82% of the faculty was in favour (strongly agreed or agreed) that statistics was really useful for research. Only 17% correctly stated that statistics is the science of uncertainty. Half of the respondents accepted that they have problem of writing the statistical section of the article. 64% of the subjects indicated that statistical teaching methods were the main reasons for the impression of its difficulties. 53% of the faculty indicated that the co-authorship of the statistician should depend upon his/her contribution in the study. Gender did not show any significant difference among the responses. However, senior faculty showed higher level of the importance for the use of statistics and difficulties of writing result section of articles as compared to junior faculty. Conclusion: The study showed a low level of knowledge, but high level of the awareness for the use of statistical techniques in research and exhibited a good level of motivation for further training. Keywords: Attitude, statistics, knowledge of medical faculty, knowledge about SPSS.